Gingival Recession: Review and Strategies in Treatment of Recession - Koppolu Pradeep; Palaparthy Rajababu; Durvasula Satyanarayana; Vidya Sagar (Case Reports in Dentistry)
One of the most common esthetic concerns associated with the periodontal tissues is gingival recession. Gingival recession is the exposure of root surfaces due to apical migration of the gingival tissue margins; gingival margin migrates apical to the cementoenamel junction. Although it rarely results in tooth loss, marginal tissue recession is associated with thermal and tactile sensitivity, esthetic complaints, and a tendency toward root caries. This paper reviews etiology, consequences, and the available surgical procedures for the coverage of exposed root surfaces, including three case reports.